Analisis Faktor yang Mempengaruhi Permudaan Alami Tumbuhan Ampupu (Eucalyptus urophylla) di Hutan Lindung Mutis Timau Kabupaten Timor Tengah Selatan Provinsi Nusa Tenggara Timur - Verianto Lango Manupele; Ludji Michael Riwu Kaho; Astin E. Mau (Wana Lestari, 2025)
The Mutis Timau Protection Forest has a poor pattern of youth regeneration. This is based on the conditions in the field which show that ampupu stands at the tree level are quite dense, while at the pole, sapling and seedling levels it is quite rare to find them, so this research was conducted to find out (1) How is the natural rejuvenation of Ampupu (Eucalyptus urophylla) in the Mutis Timau Protection Forest (2) What are the factors that affect the growth of Ampupu (Eucalyptus urophylla) natural rejuvenation in the Mutis Timau Protected Forest. This research was carried out in the Mutis Timau Protection Forest, Kuanoel Village, South Central Timor Regency, East Nusa Tenggara Province, which was conducted for 1 month, from December 2022 - January 2023. This research used methods of vegetation analysis, interviews and literature study. The results showed that the condition of the Ampupu plant in the Mutis timau Protected Forest Area. At the tree level, there are two types of trees, namely Ampupu (E. urophylla) and Kasuari (Casuarina), with the highest INP value, namely Ampupu with a value of 198.891. For the pile level there is only one type of pile, namely Ampupu (E. urophylla), with an INP value of 300. For the stake level there are two types of stakes namely Ampupu (E. urophylla) and Harendong (Melastoma malabathricum), with the highest INP value, namely Ampupu with a value 139,522 and followed by harendong with a score of 63,189. For the seedling level, there is only one type of seedling, namely Ampupu (E. urophylla) with an INP value of 200 and factors affecting the growth of the natural regeneration of the Ampupu (E. urophylla) in the Mutis Timau Protected Forest Area are illegal grazing, forest encroachment, shifting cultivation, illegal logging, and forest fires.